INTENSITAS SERANGAN HAMA ULAT GRAYAK SPODOPTERA FRUGIPERDA PADA TANAMAN JAGUNG DI KABUPATEN TAKALAR - Noerfitryani, N; Anwar, Andi Rahayu; Hamzah, H; Syamsia, S; Sampara, S (Fakultas Pertanian, Peternakan dan Perikanan Universitas Muhammadiyah Parepare, 2023)
Spodoptera frugiperda is an invasive insect and includes a highly polyphagous insect that can attack various types of plants. Armyworm attacks can be a severe threat to corn farmers. It can cause significant yield loss. This study aims to determine the attack intensity and distribution of the S. frugiperda armyworm in several sub-districts on several varieties of maize in Takalar Regency, South Sulawesi, as the first step in determining an appropriate control strategy. The results showed that from the five sub-districts where the observations were made, there were symptoms of S. frugiperda attack, namely in the sub-districts of South Polongbangkeng, North Polongbangkeng, Sanrobone, South Galesong, and Pattallassang. The highest attack intensity was around 97.33% of 4 weeks in Pallantikang Village, Pattallassang District. The lowest attack intensity, namely 46.44% of 3 weeks, was found in Kadatong Village, South Galesong District.